USING A MODULAR APPROACH IN THE CREDIT SYSTEM OF EDUCATION (Academicia Globe: Inderscience Research, 2021)
The article describes the credit system of education, which is one of the main tasks in the university today is the selection of new forms and methods of teaching, allowing not only to give the necessary knowledge, but to include the student in the system of continuous professional education and self-education.